Chytrid fungus parasitizing the wild amphibian Leptodactylus ocellatus (Anura: Leptodactylidae) in Argentina - Herrera, Raúl (2005)
The present contribution is the first report of parasitosis by a chytrid fungus in wild anuran amphibians in Argentina, as well as the first case of amphibian mortality documented to date in Argentina. We report the presence of the chytrid fungus in dead adult Leptodactylus ocellatus. It has been suggested that chytridiomycosis is the main cause of death in several amphibian populations worldwide. Our study demonstrates that chytridiomycosis afflicts L. ocellatus, a common widespread amphibian species, and is the first report of chytridiomycosis in the Argentinian lowlands. The occurrence at this latitude would indicate an extended distribution of this fungus in wildlife populations. It is also the first report of amphibian mortality due to chytrid fungus in our country. It is noteworthy that the site of collection is situated very close to sea level in a temperate climate zone and that this represents the southernmost record for South American wild amphibians.